Evaluación económica de la empresa de trajes de baño Salí Collections personalizados y comercializados online (2018)
The content of the following monograph is applied to the economic evaluation of Salí Collections for the marketing of online swimwear. This document is made in order to determine the viability of this business idea, from a market study, making an analysis of the current situation of electronic commerce in Colombia, in order to achieve a target market to which we want to focus on entrepreneurship . The description of the technical, administrative and legal assembly is made, starting from the online commercialization, establishing the characteristics of placing a micro clothing workshop in the city of Bogotá, determining the organic and administrative structure of the same and legally required to constitute the company in Colombia.